Os encantos do ventre que canta : as transversalidades do canto pré-natal na dualidade corpo-som - Vettorelo, Jéssica Melina Behne (2019)
Through a interdisciplinary approach this search investigates the practice of singing throughout the gestation, so that way unveil the steps which are inside the act of singing to the baby. It is deepened in the method of psychophony, which was created in the 1960’s by the french singer Marie Louise Aucher, and that recently has been spread in Brazil. The body dynamic, movement, sounds and music, and the amplification of body corporal conscience through the perception of sound resonances, the mouth articulation and the relationship regarding vocal apparatus and genital tracks, are some of the procedures experienced trough prenatal singing sections. About the methodologic approach, leads to be a qualitative feature of an action-research, based on bibliographic studies, practical application and audiovisual recording observation of a project developed by the researcher, entitled Belly (en)chanted, in 2018 in the Municipal Rehabilitation Center of Primavera do Leste – MT, with pregnant woman mostly attended by SUS (Single Healthy System). The procedure to collect information was done by audiovisual recording sections, to further analysis and interpretation of those practices. At the end of the research, it was possible to check some particularities and crossings during a gestation at the physiological and psychological level, understanding how part of a contemporary woman experiences motherhood.